Hydrochemical and geological model of the Bañitos-Gollete geothermal system in Valle del Cura, main Andes Cordillera of San Juan, Argentina. (December 2019) - Barcelona, H.; Lelli, M.; Norelli, F.; Peri, G.; Winocur, D.
Abstract: The main characteristics of geothermal systems at flat-slab segments are not well understood. This work reports a geological and fluid geochemistry survey at the southern thermal areas of the isolated Valle del Cura, located at the Frontal Andes Cordillera over the Pampean flat-slab. Deep circulation along deep-rooted N-S trend faults and fractures likely heats meteoric water through a locally anomalous geothermal gradient related to scattering Quaternary volcanism. Hot springs discharge up to 60 °C Na-Cl bearing water with high TDS (>5000 mg/L) from meteoric origin, according to the isotopic composition. At the top of an 11 m height travertine fissure ridge, intense gas flux is mainly composed of CO2 . Enthalpy model, δD, and B suggest a similar evolution trend for the Bañitos and Gollete thermal waters, clearly separated by the trend evidenced for thermal waters of the northern thermal sites of the Valle del Cura (e.g., Despoblados). Reservoir probably develops below 2–3 km depth hosted by the ignimbrites of the Choiyoi Group. Cation and multicomponent geothermometers estimate a temperature of ~140 °C and quartz + albite + calcite + chlorite ± beidellite-Na ± montmorillonite-K was inferred as the mineral assemblage. Very low tritium contents and δ 18 O isotopic shift might be because of the water-rock interaction process at low permeability conditions. These findings are consistent with a long residence, fault-controlled deep fluid circulation path. During their rise, the thermal waters likely interacted with cold waters at the base of the Oligocene volcanic deposits, where secondary processes such as calcite and silica precipitation may occur. Further investigations are required to assess the geothermal potential of the study areas, but we hope that this study may represent an incentive for other detailed investigations to evaluate the geothermal systems over flat-slab geothermal plays. Highlights: The thermal fluid has a meteoric source and suggests an equilibrium temperature at ~140 °C. Bañitos-Gollete shows a different fluid evolution trend than northern thermal sites. A slow and deep flow path, low permeability and fissure control characterize the system. Flat-slab geothermal play types may have medium to high enthalpy resources.